Biomimetic fiber‐reinforced composite structures based on natural plant ramifications serving as models: Biomimetische Faserverbundstrukturen inspiriert durch natürliche Pflanzenverzweigungen. Issue 11 (17th November 2016) - Schwager, H.; Neinhuis, C.
Abstract : The increasing demand for material and energy efficient products requires new strategies for designing and developing these products. For this, biomimetics is a promising approach adopting the strategies of living organisms to cope with their environmental conditions as inspiration for solving engineering problems. The evolutionary optimized biological models are often characterized by functional integration, a low environmental impact and high level of sustainability. In this paper we describe the general approach of such a biomimetic workflow on the example of topology optimization based on the model of natural ramifications. We compare the load adaptations in cactus ramifications to the load‐adaptive growth, which can be found in tree branchings. Compared to trees, the branches of columnar cacti taper towards the branch base with a pronounced constriction at the attachment point. In addition, the cactus wood features distinct indentations on the upper and lower side of the branch base which can be regarded as relief notches helping to modify the stress distribution in these regions with unfavorable fiber course. These results of our research point to a cactus specific load adaptation strategy that might be helpful for the design of fiber reinforced composite structures with restricted design space.